1995
DOI: 10.1523/jneurosci.15-03-01714.1995
|View full text |Cite
|
Sign up to set email alerts
|

The dopamine transporter: immunochemical characterization and localization in brain

Abstract: Antibodies specific for the dopamine transporter (DAT) was developed and characterized by immunoblot analysis, immunoprecipitation, and immunocytochemistry, and used for immunolocalization of transporter protein in rat brain at the light microscopic level. Antibodies targeting the N-terminus, the second extracellular loop, and the C- terminus were generated from fusion proteins containing amino acid sequences from these respective regions. Immunoblot analysis demonstrated that N-terminus and loop antibodies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

45
328
4
6

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 510 publications
(383 citation statements)
references
References 41 publications
45
328
4
6
Order By: Relevance
“…Indeed, recent studies suggest that DAT is the critical element regulating the actions of DA (Jaber et al 1997;Kuhar 1998). Thus, DAT immunoreactivity would be expected to label DA-containing axons selectively, a view supported by multiple lines of evidence in other brain regions of both rodents and primates (Ciliax et al 1995(Ciliax et al , 1999Freed et al 1995;Lewis and Sesack 1997;Sesack et al 1998). For example, the DAT antibody used in this study robustly labels the DA-containing neurons of the primate mesencephalon, but does not label any neurons that utilize other monoamines (Ciliax et al 1999;Lewis and Sesack 1997).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Indeed, recent studies suggest that DAT is the critical element regulating the actions of DA (Jaber et al 1997;Kuhar 1998). Thus, DAT immunoreactivity would be expected to label DA-containing axons selectively, a view supported by multiple lines of evidence in other brain regions of both rodents and primates (Ciliax et al 1995(Ciliax et al , 1999Freed et al 1995;Lewis and Sesack 1997;Sesack et al 1998). For example, the DAT antibody used in this study robustly labels the DA-containing neurons of the primate mesencephalon, but does not label any neurons that utilize other monoamines (Ciliax et al 1999;Lewis and Sesack 1997).…”
Section: Discussionmentioning
confidence: 70%
“…Because TH is expressed in all catecholamine-synthesizing neurons, we also evaluated the distribution of axons immunoreactive for DAT, a protein found only in DA neurons (Ciliax et al 1995;Freed et al 1995;Lewis and Sesack 1997;Sesack et al 1998). In all animals examined, axons labeled by the DAT antibody were present only in the cerebellar vermis (Fig.…”
Section: Distribution Of Dat-labeled Axonsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the dorsolateral prefrontal cortex a decrease in DA level contributed significantly to the increase in HVA/DA ratio elicited by clozapine. In the mesoprefrontal DA system, where the recapture mechanism is inefficient (Ciliax et al, 1995;Sesack et al, 1998;Lewis et al, 2001) and transmitter homeostasis is more dependent on synthesis (Galloway et al, 1986), increases in functional activity can be reflected by a decrease in transmitter as well as an increase in metabolite level (Bean and Roth, 1991). It is not entirely clear why clozapine, but not typical antipsychotic drugs such as haloperidol, has a preferential action on cortical DA systems compared to the striatal DA systems.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this disparity may be divergent transporter expression in midbrain as compared to hippocampus, most notably those transporters capable of transporting [ 3 H]5-HT. The midbrain ventral tegmental area and substantia nigra both display significant DAT expression (Mennicken et al, 1992, Ciliax et al, 1995, Freed et al, 1995, Hersch et al, 1997 and, as such, the reported kinetic analyses of 5-HT uptake into midbrain synaptosomes may reflect uptake via multiple transporters and not uptake specifically via SERT. In a more recent study, Samuvel and colleagues (2005) reported K m and V max values for 5-HT uptake into midbrain synaptosomes using 0.1 μM fluoxetine to define nonspecific uptake.…”
Section: Discussionmentioning
confidence: 99%